Conjunctures of the human and the divine will: considerations from Philonic hypothesis, contemporary theory and covenantal theology - Dr Erwin Samuel Henderson (Pharos Journal of Theology)
The research question considers what the effects of Philonic philosophy and theology are upon contemporary understanding of divine and human volition. The research methodology analyses epistemological, ontological and empirical paradigms applied to Philo’s Hellenistic natural knowledge framework as it encounters Old Testament Yahwist comprehension of the divine ontology and relationality with humanity, and to contemporary scientific and theological metaphysical hypotheses. Particular attention is paid to the radical reinterpretation and incorporation of Hellenist concepts and the effects upon future constructs. Knowledge is drawn from philosophical, theological and scientific theoretical frameworks, analysed, critiqued and correlated to congruent determinist, indeterminist and self-determinist paradigms. The apostolic-ontological framework advocates an alternative reading of causality, determinism and volition by articulating a new mode of existence demonstrated in the New Testament which, engenders new principles for divine-human inter-relatedness.